1999
DOI: 10.1080/07421222.1999.11518226
|View full text |Cite
|
Sign up to set email alerts
|

Password Security: An Empirical Study

Abstract: Organizations are more dependent than ever on the reliable operation of their information systems, which have become a key to their success and effectiveness. While the growing dependence on information systems creates an urgent need to collect information and make it accessible, the proliferation of computer technology has also spawned opportunities for ill-intentioned individuals to violate the information systems' integrity and validity.One of the most common control mechanisms for authenticating users of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 30 publications
4
131
1
2
Order By: Relevance
“…Researchers have found that password policies help users create passwords that are generally harder to crack than those created without composition requirements [11,25,32]. Unfortunately, users are frustrated by inflexible password-composition and password-management requirements [1,19], and they often fulfill requirements in predictable ways [9,28,33,35].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Researchers have found that password policies help users create passwords that are generally harder to crack than those created without composition requirements [11,25,32]. Unfortunately, users are frustrated by inflexible password-composition and password-management requirements [1,19], and they often fulfill requirements in predictable ways [9,28,33,35].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Rather than collect passwords expressly for an experiment, some researchers ask users to self-report password information, including both password composition details and user sentiment information [7,33,37,47,49,58]. While self-reported data can be very useful and can provide a lot of context, it cannot always be considered reliable, particularly with regard to a sensitive topic like passwords.…”
Section: Password Corporamentioning
confidence: 99%
“…Consequently, guessing attacks, where the attacker guesses a possible password, hashes it, and compares the hash to the stored value, are usually quite efficient. This has been realized early, and password guessing has been deployed for a long time (see, e.g, [4,39,40,15]). …”
Section: Password Securitymentioning
confidence: 99%